Schoepfia Fruit Fly, Anastrepha interrupta Stone (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; John B. Heppner (EDIS)
The schoepfia fruit fly, Anastrepha interrupta Stone, is native to southern Florida and one of six Anastrepha species which occur in or have been established in Florida at some time. The species was described from southern Florida (Stone 1942) and is thus far known only from coastal counties of south-central Florida to Key West. The schoepfia fruit fly has not been found on any economic fruits and is only known to feed on fruit of Schoepfia chrysophylloides (A. Rich.) Planch. (Olacaceae) (Weems 1967). This document is EENY-267 (originally published as DPI Entomology Circulars 61 and 327), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.